Improvement the cogging torque reduction methods by combining the magnet slotted and gradually inclined surface end in permanent magnet generator - Abduh, Syamsir; Fikri, Miftahul; Nur, Tajuddin (Institute of Advanced Engineering and Science, 2025)
Cogging torque (CT) in permanent magnet synchronous (PMS) machine, generator or electric motor should be reduced to increase the preperformance in application. Many CT reduction techniques has been proposed in the last few years. This research dealt with the study of techniques for reduction of the CT in PMSG. The PMS generator investigated in this paper is the integral slot number type with 18 slots and 6 poles. The CT has been analyzed to be reduced by employ the slot opening width variation, magnet edges slotting, and gradually inclined surface end. This paper also has analyzed the effect of combination of slot opening width and slotting permanent magnets. The finite element method magnetics (FEMM) is used in this work to perform electromagnetic simulations of the PMSG. Using the FEMM, the CT reduction of permanent magnet synchronous generators studied is analyzed and the CT peak value is compared. It is found that by combining of reduced of slot opening and slotting the permanent magnets can reduce the CT of PMS generator significantly abound 98.55% compared with the base line model.